THE PROGNOSTIC SIGNIFICANCE OF NEUTROPHIL-TOLYMPHOCYTE RATIO PATIENTS WITH LYMPHOMA - Alpay Medetalibeyoğlu; Merve Ateş; Mustafa Altınkaynak; Gazi Çapar; Sena Bayrakdar; Timur Selçuk Akpınar; Cemil Taşçıoğlu (İstanbul Tıp Fakültesi Dergisi)
Objective: The neutrophil-to-lymphocyte ratio (NLR) has been recently proposed as a simple, inexpensive prognostic factor in cancer patients. We aimed to investigate the prognostic meaning of pretreatment NLR in patients with lymphoma. Material and Method: Patients aged over 18 years with lymphoma who were diagnosed, followed-up and treated between January 2011 and December 2017 in the department of internal medicine were enrolled in this study. The data of 82 patients (62 NHL and 20 HL) were obtained retrospectively. The relationship between the NLR and baseline characteristics, laboratory parameters, prognosis, and survival outcome were evaluated. Results: In patients with HL, the older age group of the patients at the time of diagnosis had a high mortality rate and pleural effusion had a significant negative effect on OS (p=0.008, p=0.035). In patients with NHL, an advanced age, high IPI score, decreased PLT level and elevated beta 2 microglobulin were associated with a high mortality rate (p=0.001, p=0.044, p=0.023, p=0.009). Conclusion: A relation between the NLR and mortality and OS could be not demonstrated in HL patients and NHL patients. The retrospective analysis with a small sample size, late-diagnosed patients population and single-centre study may be the causes of these unexpected results.